The implementation of a portfolio assessment system for a rural clinical school in South Africa : what can be learned from the implementation of portfolios as an assessment system in a rural clinical school - Stidworthy, Jennifer Jane (Stellenbosch : Stellenbosch University, 2013)
Thesis (MPhil)--Stellenbosch University, 2013.